PELAKSANAAN PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN DI DESA KEPAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2013 - Marya Ulfa; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Law No. 40 of 2007 on Persereon Limited has mandated for every company to implement Corporate Social Responsibility program which affirmed again by Kampar Regency Regulation No. 3 of 2012 on Corporate Social Responsibility. This program is a form of corporate accountability to the people that are around the company to meet the needs of a truly very be required by community.However fact Corporate social Responsibility program conducted by PT. Agro Eternal ineffective marked with many needs of the community that are not met and the implementation of activities that are not programmed according to existing regulations.The purpose of this study was to determine the cause of the implementation of Corporate Social Responsibility program in the village of Siak Hulu Kepau Jaya District of Kampar district has not done well. In collecting the data obtained from the documentation and documentation-depth interviews with informants. Once the data is collected and then analyzed with descriptive qualitative analysis menggunankan.After doing research, the application of corporate social responsibility are implemented Pt. Agro immortal not in accordance with the mandate of the existing regulations, in which the company is not programmed CSR activities in their annual work. Then supervision undertaken by the Department of Plantation is not running. Suggestions for this problem the government should be more active in monitoring and firmly in the regulations.Keywords : Implementation, Responsibility, Corporate.